An easy-to-source, inexpensive, self-retaining anorectal retractor. Issue 3 (July 2016) - Morsi, Ahmed H.
Abstract : Objective: The aim of this study was to build a self-retaining anorectal retractor using easy-to-source components, to use in regular clinical practice. This retractor is used primarily in transanal endorectal pull-through. Materials and methods: The components used to build this retractor were as follows: a set of elastic rubber straps, a set of stainless steel fish hooks, and a frame made of acrylic (plexiglass). Every fish hook was fixed to one end of each rubber strap and used to anchor the anal mucosa. The other end of each rubber strap was stretched over the acrylic frame to achieve the desired degree of retraction. Results: The retractor is effective, providing adequate exposure of the surgical field throughout the pull-through procedure. It is light, yet robust, and reusable. Conclusion: This self-retaining anorectal retractor proved to be a simple-to-build, inexpensive, and effective surgical tool in transanal endorectal pull-through procedure.